Modeling Seepage‐Driven Bank Collapse in Fluvial and Tidal Channels - Kaili Zhang; Zheng Gong; Kun Zhao; Stefano Lanzoni; Giovanni Coco (Water Resources Research)
Abstract Groundwater flows have been recognized as an important factor controlling bank collapse in both fluvial and tidal environments. These flows are strongly related to water‐level fluctuations in the channel and contribute to seepage erosion and variations in bank soil properties. Despite the more frequent, periodic water level changes in tidal settings, seepage‐driven bank collapses of tidal channels have gained less attention as compared to their fluvial counterparts, leaving a remarkable knowledge gap in understanding the differences between these two systems. Here, we refine an established numerical model for bank collapse by including seepage dynamics and validate the model using novel data from laboratory experiments and field observations. From a mechanistic perspective, seepage‐driven bank collapse plays an equivalent role in the widening of river and tidal channels. At the same time, periodic variations in water level occur more regularly in tidal channels than in rivers, making seepage‐driven bank collapse more likely to affect tidal channels.